Teaching for Social Justice in English Language Classrooms: A Qualitative Analysis of Pedagogical Designs - John Robin H Raton; Rob Cris A Bagares; Carlo G. Soberano (Yayasan Visi Intan Permata, 2024)
Teaching for Social Justice (TSJ) is a teaching approach aimed at promoting equity and justice in language classrooms, aligned with the Philippine K to 12 Curriculum Guide (Kiger & Varpio, 2020). This integrated approach seeks to develop social awareness and critical thinking skills among learners by interrogating issues about (in)justice and indoctrination (Spitzman & Balconi, 2019). This research aims to locate the teaching of social justice in English as a Second Language (ESL) Classrooms by analyzing the 25 pedagogical designs (referring to lesson plans) of Filipino ESL teachers crafted in years 2019-2023 in a secondary school in Antipolo City, Philippines. The six-steps thematic analysis model of Kiger and Varpio (2020) complemented by the nine-question rubric developed by Spitzman and Balconi (2019) was employed to locate the integration of the teaching of social justice in the lesson plans. Peer debriefing was performed to ensure the credibility of the result. The qualitative analysis found three main themes: (1) Facilitating Expression and Constructing Identity, (2) Acknowledging Interculturalism and Diversity, and (3) Promoting Action, each of which is pedagogically organized in a plan. These themes are discursively present in the motivation, discussion, and assessment sections of the lesson plan. Findings revealed that Filipino ESL teachers’ teaching for social justice leans more toward multicultural and culturally responsive education. The study recommends the future researchers to further study TSJ in terms of confirming the consistency of teachers’ pedagogical design and action in the ESL classroom